Estimating the revenue costs of tax treaties in developing countries - Petr Jansky (Charles University in Prague, Institute of Economic Studies (IES), 2018)
Tax treaties between countries influence how much tax revenues governments receive from multinational enterprises. These treaties often reduce the withholding tax rates on outgoing dividend and interest payments. We provide illustrative estimates of costs for these two taxes for 14 developing countries in sub-Saharan Africa and Asia in a first multi-country comparison of this kind. These might be overestimates because we assume that foreign direct investments are not influenced by the tax treaties. We estimate that the highest potential tax revenue losses are within hundreds of millions USD and around 0.1% of GDP, with Philippines incurring the highest losses both in USD and relative to GDP. We also find that around 95% of the losses is due to dividends and that only four investor countries - Japan, Netherlands, Switzerland, and Singapore - are together responsible for more than half of the losses. We discuss the limitations of these estimates and how future research could improve their quality as well as coverage.
Keywords: F21; F23; H25; H26; 330; foreign direct investment; multinational enterprises; tax treaty; double taxation agreement; withholding tax; developing countries